Extending instrumental sea-level records using coral microatolls, an example from Southeast Asia - Majewski, Jędrzej M. (2022)
The small number of reliable long-term (i.e., >50 yrs) tide gauges in tropical locations is a major source of uncertainty in modern sea-level change. Coral microatolls record relative sea-level (RSL) change over their lifetimes and have the potential to extend the instrumental record. Here, we examined a 20th and 21st century RSL record from two living coral microatolls from Mapur Island, Indonesia, which produced 16 sea-level index points. We validated and combined the living coral microatoll data with tide gauge data to show RSL at Mapur Island was 0.0 ± 1.6 mm/yr (2σ) from 1915 to 1990 and 1.0 ± 2.1 mm/yr (2σ) from 1990 to 2019. Through the addition of microatoll RSL data we extended the record of modern sea-level change by over 50 years and reduced its uncertainty by ∼50%.